Numerous Fasciola plasminogen-binding proteins may underlie blood-brain barrier leakage and explain neurological disorder complexity and heterogeneity in the acute and chronic phases of human fascioliasis. Issue 3 (24th September 2018) - González-Miguel, J.; Valero, M. A.; Reguera-Gomez, M.; Mas-Bargues, C.; Bargues, M. D.; Simón, F.; Mas-Coma, S.
Abstract: Human fascioliasis is a worldwide, pathogenic food-borne trematodiasis. Impressive clinical pictures comprising puzzling polymorphisms, manifestation multifocality, disease evolution changes, sequelae and mortality, have been reported in patients presenting with neurological, meningeal, neuropsychic and ocular disorders caused at distance by flukes infecting the liver. Proteomic and mass spectrometry analyses of the Fasciola hepatica excretome/secretome identified numerous, several new, plasminogen-binding proteins enhancing plasmin generation. This may underlie blood-brain barrier leakage whether by many simultaneously migrating, small-sized juvenile flukes in the acute phase, or by breakage of encapsulating formations triggered by single worm tracks in the chronic phase. Blood-brain barrier leakages may subsequently occur due to a fibrinolytic system-dependent mechanism involving plasmin-dependent generation of the proinflammatory peptide bradykinin and activation of bradykinin B2 receptors, after different plasminogen-binding protein agglomeration waves. Interactions between diverse parasitic situations and non-imbalancing fibrinolysis system alterations are for the first time proposed that explain the complexity, heterogeneity and timely variations of neurological disorders. Additionally, inflammation and dilation of blood vessels may be due to contact system–dependent generation bradykinin. This baseline allows for search of indicators to detect neurological risk in fascioliasis patients and experimental work on antifibrinolytic treatments or B2 receptor antagonists for preventing blood-brain barrier leakage.